Sequence composition of BAC clones and SSR markers mapped to Upland cotton chromosomes 11 and 21 targeting resistance to soil-borne pathogens - Wang, Congli; Ulloa, Mauricio; Shi, Xinyi; Yuan, Xiaohui; Saski, Christopher; Yu, John Z.; Roberts, Philip A. (Frontiers in Plant Science, 2015)
Genetic and physical framework mapping in cotton (Gossypium spp.) were used to discover putative gene sequences involved in resistance to common soil-borne pathogens. Chromosome (Chr) 11 and its homoeologous Chr 21 of Upland cotton (G. hirsutum) are foci for discovery of resistance (R) or pathogen-induced R (PR) genes underlying QTLs involved in response to root-knot nematode (Meloidogyne incognita), reniform nematode (Rotylenchulus reniformis), Fusarium wilt (Fusarium oxysporum f.sp. vasinfectum), Verticillium wilt (Verticillium dahliae), and black root rot (Thielaviopsis basicola). Simple sequence repeat (SSR) markers and bacterial artificial chromosome (BAC) clones from a BAC library developed from the Upland cotton Acala Maxxa were mapped on Chr 11 and Chr 21. DNA sequence through Gene Ontology (GO) of 99 of 256 Chr 11 and 109 of 239 Chr 21 previously mapped SSRs revealed response elements to internal and external stimulus, stress, signaling process, and cell death. The reconciliation between genetic and physical mapping of gene annotations from new DNA sequences of 20 BAC clones revealed 467 (Chr 11) and 285 (Chr 21) G. hirsutum putative coding sequences, plus 146 (Chr 11) and 98 (Chr 21) predicted genes. GO functional profiling of Unigenes uncovered genes involved in different metabolic functions and stress response elements (SRE). Our results revealed that Chrs 11 and 21 harbor resistance gene rich genomic regions. Sequence comparisons with the ancestral diploid D5 (G. raimondii), A2 (G. arboreum) and domesticated tetraploid TM-1 AD1 (G. hirsutum) genomes revealed abundance of transposable elements and confirmed the richness of resistance gene motifs in these chromosomes. The sequence information of SSR markers and BAC clones and the genetic mapping of BAC clones provide enhanced genetic and physical frameworks of resistance gene-rich regions of the cotton genome, thereby aiding discovery of R and PR genes and breeding for resistance to cotton diseases.